Fast food consumption and risk of non-alcoholic fatty liver disease: a systematic review and meta-analysis - He, Jinke; Wang, Yingxue; Weng, Fangbin (Frontiers in Public Health, 2025)
BackgroundNon-alcoholic fatty liver disease (NAFLD) is a global health issue, with fast food consumption hypothesized as a risk factor. This meta-analysis aimed to explore the relationship between fast food intake and NAFLD.MethodsThis review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. A comprehensive search was conducted across PubMed, Web of Science, Scopus, and Embase from inception to February 28, 2025. A total of nine eligible observational studies involving 169,771 participants were included. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using random-effects models.ResultsA higher consumption of fast food was significantly associated with a 55% increased risk of NAFLD (OR = 1.55, 95% CI: 1.51–1.59, p < 0.001, I2 = 15.6%). Moreover, fast food intake was linked to a 37% higher risk of obesity (OR = 1.37, 95% CI: 1.27–1.49, p < 0.001, I2 = 54.2%), a key metabolic factor in NAFLD pathogenesis. Sensitivity analysis confirmed the robustness of these associations, with no significant evidence of publication bias.ConclusionFast food consumption is positively associated with NAFLD and obesity. Heterogeneity highlights the need for standardized methods in future large-scale studies to validate these findings and inform preventive strategies.